Efficacy of Divinylbenzenic Resin in Removing Indoxyl Sulfate and P-cresol Sulfate in Hemodialysis Patients: Results from an In Vitro Study and an In Vivo Pilot Trial (xuanro4-Nature 3.2) - Maria Teresa Rocchetti; Carmela Cosola; Ighli di Bari; Stefania Magnani; Vanessa Galleggiante; Letizia Scandiffio; Giuseppe Dalfino; Giuseppe Stefano Netti; Mauro Atti; Roberto Corciulo; Loreto Gesualdo (Toxins, 2020)
High serum levels of microbiota-derived uremic toxins, indoxyl sulfate (IS) and p-cresyl sulfate (PCS), are associated with chronic kidney disease (CKD) progression and cardiovascular complications. IS and PCS cannot be efficiently removed by conventional hemodialysis (HD), due to their high binding affinity for albumin. This study evaluates the efficacy of a divinylbenzene-polyvinylpyrrolidone (DVB-PVP) cartridge and a synbiotic to reduce uremic toxins in HD patients. First, the in vitro efficacy of DVB-PVP in adsorbing IS and PCS was evaluated. Second, a randomized, placebo-controlled pilot study in HD patients was carried out to establish whether the administration of a synbiotic, either individually and in association with DVB-PVP-HD, could reduce the production of uremic toxins. In vitro data showed that DVB-PVP resin removed a mean of 56% PCS and around 54% IS, after 6 h of perfusion. While, in the in vivo study, the DVB-PVP cartridge showed its adsorbing efficacy only for IS plasma levels. The combination of synbiotic treatment with DVB-PVP HD decreased IS and PCS both at pre- and post-dialysis levels. In conclusion, this study provides the first line of evidence on the synergistic action of gut microbiota modulation and an innovative absorption-based approach in HD patients, aimed at reducing plasma levels of IS and PCS.